L’enquête sur la situation matérielle et morale de l’enfant délinquant : l’exemple du tribunal de Grasse (1912-1922) - Gwenaëlle Callemein (Criminocorpus)
The law of 22 July 1912 requires the judge conduct an investigation into the material and moral situation of the child and their family when the former is suspected of having committed an infraction. This new investigation is essential in the pronouncement of the decision and it is interesting to determine what are the elements sought by the judge to draw up the profile of the minor and know to whom he entrusts these investigative measures. The sources contained in the departmental archives of the Alpes-Maritimes provide an example of the issues of investigation when the offender is a minor and an apportunity to appreciate, from the resultats of the inquest, the ideas we have about children’s guilt.